Learning management systems and their impact on academic work. Issue 3 (26th May 2020) - Brady, Malcolm; O'Reilly, Naoimh
ABSTRACT: Enterprise-wide, repository-based, ubiquitously available, socially oriented technologies such as learning management systems (LMSs) and virtual learning environments are altering the nature of institutional teaching and learning processes. These technology-induced changes are likely in turn to have an impact on the work experience of academics. This article qualitatively examines the impact of LMSs on several important academic relationships: with students, with colleagues, with the institution itself and with home. The research found that academics mainly used LMSs as repositories of materials with some additional use for managing assessment; however, they made little use of communication, administration or monitoring features. Academics used LMSs in ways and for purposes that suited themselves: use of LMSs has not changed teaching habits or approaches. Academics were not concerned about the impact of the technology on home–life or work–life balance. Academics reported little concern about intellectual property but nevertheless took measures to protect teaching materials.